Chromium isotope evidence for oxygenation events in the Ediacaran ocean. (15th April 2022) - Xu, Dongtao; Wang, Xinqiang; Zhu, Jian-Ming; Jiang, Ganqing; Shi, Xiaoying; Wang, Xiangli; Sahoo, Swapan K.
Abstract: Pulses of the Ediacaran ocean oxygenation were inferred from strong enrichments of redox-sensitive elements (RSEs; particularly Mo, V, U, Re) and negative pyrite sulfur isotopes (δ 34 Spy ) in black shales of the Doushantuo Formation in South China. These oceanic oxygenation events (OOEs) have been challenged by the lack of comparable RSE enrichments in correlative strata of northwestern Canada. Here we report four positive chromium isotope (δ 53 Cr) excursions with peak values (+0.79 ± 0.03‰ to +1.45 ± 0.06‰; 2SD) close to the average δ 53 Cr value of the modern ocean (+1.0 ± 0.3‰) at the intervals of OOEs, which are separated by low δ 53 Cr values close to that of the bulk silicate Earth (BSE, −0.124 ± 0.101‰). The positive δ 53 Cr excursions could be explained by episodic input of oxygenated water from the open ocean to the restricted Nanhua basin, or pulses of ocean oxygenation during the Ediacaran-early Cambrian. The two interpretations can explain the majority of the geochemical data available from the Wuhe section, but both have limitations. The first interpretation implies that the open ocean was more oxygenated than the Nanhua basin during the entire Ediacaran-early Cambrian period, which is not supported by the currently available data from other Ediacaran successions. The second interpretation has difficulties to explain the thallium isotope (ε 205 Tl) data from the same section, pending confirmation of the OOEs from other successions globally. The data from the Wuhe section highlight the complexity of interpreting the redox history of the global ocean from geochemical results of a single section. Nonetheless, the synchronous changes of multiproxy records—including positive δ 53 Cr excursions, RSE peaks, negative δ 34 Spy and molybdenum isotope (δ 98 Mo) excursions—at the same stratigraphic intervals do support a more oxygenated ocean at 635 Ma, 580 Ma, 560 Ma, and early Cambrian, regardless of the degree of restriction of the Nanhua basin from the open ocean.